Correlación entre tiempo de conservación y perdida proporcional de poder antigénico en sueros de anuros - Cei, José Miguel Alfredo María (1970)
Antigenic activity of the Batrachian serum proteins decreases in agreement with the aging of the iced sera. The strongest progressive lost of antigenic activity in the precipitin tests is showed by Pliyllomedxisa, followed by Bufo arenarum, being the lowest lost showed by Lepto dactylus. General conclusions on the fitness of the serological reactions are exposed.